Exploring healthcare workers’ immunisation behaviour towards COVID-19 vaccines through psychological patterns - Nour El Houda Benkaddour; Sara Ramdani; Hind Khalil; Asmae Lekfif; Naima Abda; Bouchra Oneib; Yassamine Bentata (African Journal of Primary Health Care & Family Medicine)
Background: The psychological approach can provide valuable insights into vaccination behaviour, especially in high-risk contexts. It offers new perspectives for effective interventions to improve vaccination behaviour.